Effects of denosumab on pain and analgesic use in giant cell tumor of bone: Interim results from a phase II study. (September 2014) - Martin-Broto, Javier; Cleeland, Charles S.; Glare, Paul A.; Engellau, Jacob; Skubitz, Keith M.; Blum, Ronald H.; Ganjoo, Kristin N.; Staddon, Arthur; Dominkus, Martin; Feng, Amy; Qian, Yi; Braun, Ada; et al.
Abstract Background. Giant cell tumor of bone (GCTB) is an aggressive primary osteolytic tumor. GCTB often involves the epiphysis, usually causing substantial pain and functional disability. Denosumab, a fully human monoclonal antibody against receptor activator of nuclear factor κΒ ligand (RANKL), is an effective treatment option for patients with advanced GCTB. This analysis of data from an ongoing, open-label study describes denosumab's effects on pain and analgesic use in patients with GCTB. Material and methods. Patients with unresectable disease (e.g. sacral or spinal GCTB, or multiple lesions including pulmonary metastases) were enrolled into Cohort 1 (N = 170), and patients with resectable disease whose planned surgery was associated with severe morbidity (e.g. joint resection, limb amputation, or hemipelvectomy) were enrolled into Cohort 2 (N = 101). Patients received denosumab (120 mg) subcutaneously every four weeks, with additional doses on study days 8 and 15. Patients assessed worst pain severity with the Brief Pain Inventory – Short Form (BPI-SF) at baseline, at each visit for the first six months, and every three months thereafter. Results. Clinically relevant pain improvement was reported by 29% of patients in Cohort 1 and 35% in Cohort 2 during week 1 and by ≥ 50% of patients in each cohort at each study visit from months 2–30. Median time to clinically relevant improvement was 30 (95% CI 16, 57) days in Cohort 1 and 15 (95% CI 15, 29) days in Cohort 2. Results in patients with moderate/severe pain at baseline were similar. Fewer than 30% of patients in Cohort 1 and 10% in Cohort 2 experienced clinically relevant pain worsening at any visit through 27 months. Most patients had no/low analgesic use during the study. Conclusion. Most patients treated with denosumab experienced clinically relevant decreases in pain within two months.